Older Adults in an LGBT Residential Community: Impact of a Safe Space on Occupation and Well-Being - Daniel Swiatek; Sheryl Ryan; Terry Peralta-Catipon (Scholarworks @ WMU, 2021)
Background: LGBT seniors have suffered a lifetime of societal and institutional discrimination and health care inequalities. The number of LGBT people 50 years of age and older will surpass five million in the coming decades. LGBT seniors are at greater risk of disability, isolation, physical and mental health issues, and substance abuse. Supportive social environments and networks are correlated with higher quality of life. The purpose of this study was to better understand how living in a safe and secure apartment community specifically for low-income LGBT older adults impacted the residents' daily life and well-being. Method: This study was designed as a qualitative, single intrinsic case study using photo-elicitation and focus groups with residents in the nation's first low-income housing complex for LGBT older adults. Results: Data analysis generated five themes: (a) pride and expanded community, (b) improved occupational participation, (c) safety, (d) domestic independence, and (e) control over end-of-life decision-making. Conclusion: The results emphasize the importance of housing affordability, safety, and community level social acceptance as necessary for LGBT older adults. In addition, it was found that personal expression, occupation-based activities for creativity, and community spaces for LGBT older adults contributed toward greater well-being and expanded occupational participation.